(untitled) (Fiep Bulletin - online, 2013)
Defined as a phenomenon related to the work, WRMD/RSI, corresponds to a group of musculoskeletal disorders that have common features as the pain and functional impairment temporary and permanent. And as a group of diseases that are difficult to diagnosis and treatment, since many patients remain symptomatic both during and after the treatment, taking gradual evolution pathology. The objective of the present study was to verify and assess the current clinical symptomatology submitted by twelve individuals, members of the ADVERT - APLER of Umuarama, Paraná, aging from 34 to 50 years, of both sexes, affected by WRMD/RSI, participated in a study on the use of auriculotherapy in the treatment of WRMD held in 2005. The results obtained in the revaluation in 2008 showed that most participants of the search even after a prolonged period of time as the end of the treatment of auricular therapy (three years) is still benefiting from the effects promoted by the use of technology in their treatment. As can be observed today in a sampling maintenance and / or significant reduction in the intensity of pain, drugs intake, symptom incidence and painful point location, maintenance and modification of the symptomatology and characteristics of pain among others compared the results of the initial assessment and end of 2005 with the results of the revaluation of 2008. It can if you concluded from the findings of this research, that auriculotherapy has a long continuous and sustained addition to being an effective technique in dealing with cases of WRMD/RSI.